Perlindungan Hukum Bagi Pelaku Usaha Online jika Terjadi Wanprestasi yang dilakukan oleh Pemberi Jasa Endorse - I Putu Dipta Indrayana; I Nyoman Putu Budiartha; Ni Made Jaya Senastri (Jurnal Interpretasi Hukum, 2021)
The internet and social media networks are also used as a means of economic development through business for the community. Business development is carried out by business actors by means of endorsements, where in the endorsement there is a Cooperation agreement between business actors and endorsement service providers. In this cooperation, there are often defaults made by endorse service providers. In this regard, two problem formulations can be formulated, namely: What is the form of protection for online business actors in the event of default by endorsement service providers and how the legal remedies for default settlement made by endorsement service providers against online business actors. The research method in writing is normative and empirical law research. With a statutory approach, a factual approach and a case approach. This research concludes that the form of protection for online business actors in the event of default by endorse service providers is carried out by preventive and repressive measures, the way to solve the problem is done by sending three subpoena or warning to the endorse service provider, and if the endorse service provider does not have in good faith, then the settlement can be done through litigation or court.